Mangrove and coastal environment of Selangor, Malaysia - Sasekumar A.; Chong, Ving Ching (Monograph series (Universiti Malaya. Institute of Ocean and Earth Sciences), 2012)
20 articles in this book, grouped in four sections, highlight the salient features of Selangor's coastal environment.